Análisis de eficiencia en el sistema hotelero Epa\~nol: Una aplicación al caso de Sol Meliá - M. I. Alonso de Magdaleno; Marta Fernández Barcala; Manuel González Díaz (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2009)
The aim of this paper is to analyze if the choice of different mechanisms of governance affects the efficiency of hotel chain from the Transaction Cost Economics perspective. The analysis has been carried out using Data Envelopment Analysis (DEA) on the Spanish leader hotel company, Sol Meliá. Results suggest that all the establishment of this hotel chain obtain high levels of efficiency but we cannot conclude that a particular type of mechanism of governance is more efficient than others. We conclude then that the choice of the mechanism of governance does not affect the level of efficiency in this particular case. It seems that other technical variables are more relevant than the type of contract used to manage the establishments.
Keywords: 330; efficiency; DEA; hotel system; Sol Meliá; contractuals forms